DETERMINATION OF RUTIN IN LEAVES OF SALIX TRIANDRA USING THE METHOD OF PLANAR CHROMATOGRAPHY - E. G. Sannikova; T. D. Mezenova (Фармация и фармакология (Пятигорск), 2016)
The aim of the study is to develop new methods of identification and quantitative determination of rutin in the leaves of Salix triandra L. with thin-layer chromatography. The digital processing of the chromatograms was performed using «Sorbfil Videodensitometer» computer program (Krasnodar). For the chromatography analysis we used plates «Sorbfil» PTSH-P-A-UV, mobile phase: n-butanol-glacial acetic acid-water (4:1:1), detecting reagent – ammonia vapors. The rutin is detected as yellow spots with Rf 0.64±0.02. The detection limit is 0.5 μg/μl. The regression equation has the form: S=4.75×103 m. With the use of this method we found that the composition of rutin in leaves of Salix triandra was in the range 1.81±0.06% on the air-dry raw material (relative standard deviation RSD%=2.5%; the measurement error E=3.12%). The method is sensitive, linear, has a small error, and does not require expensive equipment.